Where to place the rewards? Exploration bias in mice influences performance in the classic hole-board spatial memory test - Sampedro-Piquero, Patricia; Mañas-Padilla, María del Carmen; Ávila-Gámiz, Fabiola; Gil Rodríguez, Sara; Santín-Núñez, Luis Javier; Castilla-Ortega, María Estela (Springer, 2019)
The classic hole-board paradigm (a square arena with 16 holes arranged equidistantly in a 4x4 pattern) assesses both exploration and spatial memory in rodents. For spatial memory training, food rewards are hidden in a fixed set of holes. The animal must not visit (i.e. nose-poke) the holes that are never baited (reference memory; RM) nor re-visit a baited hole within a session (working memory; WM). However, previous exploratory bias may affect performance during reward searching. During habituation sessions with either all holes rewarded or all holes empty, mice intrinsically preferred poking peripheral holes (especially those located in the maze’s corners) over centre holes. During spatial memory training, mice progressively shifted their hole pokes and staying time to the central area that contained hidden rewards, while mice exposed to the empty apparatus still preferred the periphery. A group of pseudotrained mice, for whom rewards were located randomly throughout the maze, also increased their central preference. Furthermore, reward location influenced memory measures. Most repeated pokes (WM-errors) were scored in the locations that were most intrinsically appealing to mice (i.e. the corner and wall baited holes), supporting a strong influence of previous exploratory bias. Regarding RM, finding rewards located in the centre holes, which were initially less preferred, entailed more difficulty and required more trials to learn. This outcome was confirmed by a second experiment that varied the pattern of rewarded holes, as well as the starting positions. Therefore, reward location is a relevant aspect to consider when designing a hole-board memory task.
Author manuscript
Keywords: Memoria; Ratones de laboratorio; Habituation; Periphery; Anxiety; Corner; Reference memory; Working memory